Sistem Alih Media pada Koleksi Khusus Bung Hatta di UPT Perpustakaan Proklamator Bung Hatta Bukittinggi - Putra, Aldo Maha; Desriyeni, Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2019)
Abstract The writing of this paper aims to explain the process of media transfer in the special collection of Bung Hatta and find out the obstacles that occur in the process of media transfer in the special collection of Bung Hatta and to know the efforts to overcome the obstacles in the process of media transfer in the special collection of Bung Hatta in the Bung Hatta Library Proclamation Unit. This type of research is descriptive in nature, which wants to describe the activities of digital media transfer as an effort to preserve the special collection of Bung Hatta at the Bung Hatta Library Proclamation Unit. Data collection techniques through direct observation to the location and interviews and data collection by reading and studying sources in the form of books, literature, and literature studies. Based on the processed data it can be concluded that. First, the process of media transfer activities at the Bung Hatta special collection at the Bung Hatta Library was carried out in three stages, namely: (a) the process of taking pictures (b) the editing process, and (c) the process of packaging the book for media transfer. Second, the obstacles that occur in the process of media transfer in the special collection of Bung Hatta in the Bung Hatta Proclamator Library are: (a) facilities and infrastructure that are still inadequate, (b) lack of expertise in carrying out media transfer activities in the Bung Hatta special collection, and (c) media transfer activities have not been included in the library budget. Third, the efforts made to overcome the obstacles in the process of media transfer at the special collection of Bung Hatta at the Bung Hatta Library Proclamation Unit UPT are: (a) completing facilities and infrastructure to support media transfer activities as well as preparing special rooms that are impermeable to light, (b) adding energy experts and also conduct training for other staff, and (c) incorporate media transfer activities into the library budget so that these activities run optimally and sustainably.Â Keywords: Transferring Media, Bung Hatta's Special Collection